The Effect of Nonstoichiometry on the Initial Sintering Kinetics of MnO₁₊ᵪ - Porter, Lawrence Richard (My University, 1978)
A study has been made of the initial stage sintering kinetics of nonstoichiometric MnO as a function of the oxygen partial pressure. The shrinkage and neck growth were measured for pairs of oxide spheres in the temperature range 900-1100°C and pressure range 10ˉ¹⁴
The shrinkage was analyzed using both the classical single mechanism control approach and the more recent simultaneous mechanism approach. It was found that the sintering behavior as a function of oxygen pressure, hence the concentration of Mn vacancies, does not follow a simple relationship has been suggested. The kinetics indicate grain boundary diffusIon control at oxygen pressures less than 10ˉ¹² atm. and greater than 10ˉ⁹ atm. and volume diffusion control at pressures in between.
Using the simultaneous mechanism approach, the predominance of grain boundary control at low and high oxygen pressures was verified; however, a substantial contribution from volume diffusion was present. The volume diffusion contribution reached a maximum at 1 x 10ˉ¹⁰ atm., the same pressure at which the maximum shrinkage and shrinkage rate was found.
Diffusion coefficients calculated from both methods of analysis agree well with published values and with the published defect structure for MnO.
The surface topography of the spheres was studied. It was found to influence the sintering behavior substantially and to be dependent on the atmosphere composition. A qualitative model for the effect of surface topography is presented.
Keywords: Materials Science and Engineering; Metallurgy; Materials Science and Engineering